1983
DOI: 10.1172/jci110897
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying CO2 retention during flow-resistive loading in patients with chronic obstructive pulmonary disease.

Abstract: A B S T R A C T The present study examined the respiratory responses involved in the maintenance of eucapnea during acute airway obstruction in 12 patients with chronic obstructive disease (COPD) and 3 agematched normal subjects. Acute airway obstruction was produced by application of external flow-resistive loads (2.5 to 30 cm H20/liter per s) throughout inspiration and expiration while subjects breathed 100% 02. Application of loads of increasing severity caused progressive increases in Pco2 in the patients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…10 On the other hand, a study assessing the effect of inspiratory and expiratory loading on COPD patients demonstrated that some patients could compensate for added loads, whereas other patients developed a fall in V T and a rise in PaCO 2 . 118 Comparison of these two groups revealed no difference in airflow limitation, but a significantly lower PI max in the group that was unable to compensate for the added loads. 118 Various measurements have been used to evaluate impending versus overt respiratory muscle fatigue.…”
Section: Effect Of Respiratory Muscle Dysfunction On Fatigue and Respmentioning
confidence: 90%
See 1 more Smart Citation
“…10 On the other hand, a study assessing the effect of inspiratory and expiratory loading on COPD patients demonstrated that some patients could compensate for added loads, whereas other patients developed a fall in V T and a rise in PaCO 2 . 118 Comparison of these two groups revealed no difference in airflow limitation, but a significantly lower PI max in the group that was unable to compensate for the added loads. 118 Various measurements have been used to evaluate impending versus overt respiratory muscle fatigue.…”
Section: Effect Of Respiratory Muscle Dysfunction On Fatigue and Respmentioning
confidence: 90%
“…118 Comparison of these two groups revealed no difference in airflow limitation, but a significantly lower PI max in the group that was unable to compensate for the added loads. 118 Various measurements have been used to evaluate impending versus overt respiratory muscle fatigue. Impending fatigue implies that overt fatigue is likely to develop if no change is made in the demands on the respiratory muscles.…”
Section: Effect Of Respiratory Muscle Dysfunction On Fatigue and Respmentioning
confidence: 90%
“…Acute exacerbations of COPD (aeCOPD) constitute a significant cause of morbidity and mortality among these patients. Patients with moderate to severe acute exacerbations develop alveolar hyperinflation that may lead to increased work of breathing, muscle fatigue, and hypercapnia, creating a vicious loop refractory to medical treatment [25][26][27]. The standard respiratory support in this setting in order to break this cycle is noninvasive ventilation (NIV).…”
Section: Ecco 2 R Common Configurations (A) Minimally Invasive Veno-mentioning
confidence: 99%
“…The increase in very high VȦ/Q̇ or physiological dead space is associated with elevated levels of arterial carbon dioxide [66]. Rapid shallow breathing may also be a contributor to high VȦ/Q̇ [67,68]. If ALPE is to be used in patients suffering from COPD, description of high VȦ/Q̇ must be included.…”
Section: Identification Of Challenges In Relation To Application Of Amentioning
confidence: 99%